Nurse scheduling by forward Dynamic Programming approach / Siti Aishah Sarman, Siti Farahanah Zaki and Nik Nur Salsabila Ahmad - Sarman, Siti Aishah; Zaki, Siti Farahanah; Ahmad, Nik Nur Salsabila (2019)
Nurse Scheduling Problem (NSP) is a complex problem and it is a difficult process to construct an effective schedule, which must consider all of the hospital's requirements and nurses' preferences. However, most hospitals and healthcare facilities construct the schedules manually which does not acknowledge the hospital's requirements. Therefore, they have difficulties in generating the schedule due to the issues that crop up after. Hence, a study on NSP is conducted to find the suitable method to solve NSP compared to manually made schedule. The purpose of this study is to analyze current manually made schedule with respect to the total day shift, total night shift and total working day and to determine the maximum working day and night shifts for each nurse by Dynamic Programming (DP) approach. This complex problem is divided to 13 states and four stages. The problem is solved recursively where the solution from previous stage will be used in the next stage. For instance, the solution obtained in stage one is carry forward to stage two where it is used to find the solution for stage two and this process is repeated for the next stage three and four until the final optimal solution is obtained. The result from this study indicates that DP method is compatible to find the maximum working day and night shifts for each nurse in solving NSP.